2019
DOI: 10.14202/vetworld.2019.331-336
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and molecular characterization of Mannheimia haemolytica and Pasteurella multocida associated with pneumonia of goats in Chhattisgarh

Abstract: Aim: The purpose of this study was to isolate and characterize the Mannheimia haemolytica and Pasteurella multocida from blood, nasal discharge, and lung tissue of pneumonic goats. Materials and Methods: A total of 14 goats were investigated for pneumonic pasteurellosis. Of 14 goats, nasal swabs and blood samples were collected from 10 clinically diseased animals. Moreover, lung tissue and heart blood samples were collected during necropsy of four goats died with pneumonia. All the samples were processed for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 25 publications
(27 reference statements)
3
11
0
Order By: Relevance
“…Two animals died without manifestation of any clinical sign. The clinical signs observed in the present study were almost similar to those reported earlier [10] . The manifestation of acute respiratory distress usually appears within 10-14 days in adult ruminants after exposed to stressful conditions.…”
Section: Clinical Signsupporting
confidence: 91%
See 1 more Smart Citation
“…Two animals died without manifestation of any clinical sign. The clinical signs observed in the present study were almost similar to those reported earlier [10] . The manifestation of acute respiratory distress usually appears within 10-14 days in adult ruminants after exposed to stressful conditions.…”
Section: Clinical Signsupporting
confidence: 91%
“…The results observed were typical to those exhibited by Mannhemia spp. Involvement of Pasteurella multocida and Mannhemia haemolytica in pneumonic goats has also been reported from Chhattisgarh [10] and Western Maharashtra [18] . Pneumonia in small ruminants is primarily caused by parainfluenza-3 virus and respiratory syncytial virus and mycoplasma infection and is predisposed by variable weather conditions [14] .…”
Section: Culture and Biochemical Characteristicsmentioning
confidence: 77%
“…These two dominant bacteria, Mannheimia (18.33%) and Bibersteinia (13.63%), are pathogenic microorganisms. Mannheimia haemolytica and Bibersteinia trehalosi are the main causes of pneumonia in sheep and goats of all ages, and can induce septicemia in lambs or kids [35,36]. The results revealed that kids born in a natural environment without quarantine might easily acquire pathogenic microorganisms.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing prevalence of respiratory infection in small ruminants even after HS and PPR vaccination was a serious concern. Recently respiratory infection outbreaks due to M. haemolytica and P. multocida have been reported in various states of India [ 22 , 23 ]. In the present study, we investigated the involvement of M. haemolytica and P. multocida with the respiratory infection of sheep.…”
Section: Discussionmentioning
confidence: 99%